2000
DOI: 10.1097/00000478-200011000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal NK/T-cell Lymphomas in the United States

Abstract: Sinonasal natural killer (NK)/T-cell lymphomas are common in Asia and areas of South and Central America but are rarely seen in the United States, where they have not been as well characterized. Fifteen cases diagnosed in Southern California were studied with respect to histologic features, immunophenotype, Epstein-Barr virus EBER in-situ hybridization (EBV EBER-ISH), and T-cell receptor gamma chain (TCR-gamma) gene rearrangement. Although ethnic background was available for only seven patients, six were of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
1
12

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 37 publications
7
71
1
12
Order By: Relevance
“…The nasal-type NK/TCL in this study showed clinicopathologic findings similar to those of previous studies in Asian and Western countries. 8,15,19,20 In all, 82% of our cases presented with stage I and II disease, while 18% had stage III and IV disease at presentation. The sites of initial involvement included upper aerodigestive tract, skin, gastrointestinal tract, liver, spleen, bone marrow, testis, lung, brain and soft tissue.…”
Section: Survivalmentioning
confidence: 76%
See 2 more Smart Citations
“…The nasal-type NK/TCL in this study showed clinicopathologic findings similar to those of previous studies in Asian and Western countries. 8,15,19,20 In all, 82% of our cases presented with stage I and II disease, while 18% had stage III and IV disease at presentation. The sites of initial involvement included upper aerodigestive tract, skin, gastrointestinal tract, liver, spleen, bone marrow, testis, lung, brain and soft tissue.…”
Section: Survivalmentioning
confidence: 76%
“…However, a minority of these tumors with indistinguishable clinical, histologic and immunophenotypic features may express a T-cell phenotype and show monoclonal T-cell receptor gene rearrangement. 1,2,6,19 A recent study described the presence of restricted killer immunoglobulin-like receptor repertoire and monoclonal T-cell receptor gene rearrangement in six out of 15 cases of sinonasal lymphomas, suggesting a mixed NK/T-cell differentiation in a subset of these tumors. 32 The cell lineage of NK/TCL has been evaluated in several studies using molecular genetic techniques.…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The features of these cases have been previously reported with regard to clinical presentation, histology, immunophenotype, in situ hybridization for EBV-encoded RNA (EBER-ISH), and T-cell receptor gamma chain gene rearrangement (Gaal et al, 2000). All cases were positive for EBV EBER-ISH.…”
Section: Casesmentioning
confidence: 78%
“…NL occur uncommonly in the U.S. but share identical morphologic, immunohistochemical, and molecular features with their more frequent counterparts in Asia and certain South and Central American populations (Arber et al, 1993;Gaal et al, 2000;Jaffe et al, 1996). Characterization of EBV polymorphisms to assess for tumorigenic strains or association with specific tumor types has been more extensively studied in other EBV-associated malignancies.…”
Section: Discussionmentioning
confidence: 99%